Battery pole surface microstructure, preparation method and device

By accurately controlling the laser processing parameters, a groove with a larger groove depth to the groove width ratio of the surface of the battery electrode sheet is formed, which solves the difficulties in the depth and aspect ratio and processing efficiency of the surface of the lithium-ion battery electrode sheet, and improves the charging and discharge performance and service life of the battery.

CN118969958BActive Publication Date: 2025-03-18NANJING KLIGHT LASER TECH CO LTD
View PDF 4 Cites 0 Cited by

Patent Information

Application Number
CN202411441563.4
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-10-16
Publication Date
2025-03-18
Estimated Expiration
2044-10-16

AI Technical Summary

Technical Problem

The prior art has difficulties in improving the aspect ratio and processing efficiency of the surface microstructure of lithium-ion battery sheets, resulting in difficulty in wetting the electrolyte, slowing lithium ion transmission and reduced battery energy density.

Method used

By comprehensively and accurately controlling the energy density, spot shape and pulse duration of the laser, grooves with a larger groove depth to groove width ratio are processed to form a hydrophilic structure, improving the wettability of the battery electrode sheet and generating a lithium ion fast channel.

Benefits of technology

It improves the battery's charging and discharging speed, energy density and capacity retention rate, extends the battery's service life during fast charging, and reduces cracks and powdering of the pole sheet.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN118969958B_ABST
    Figure CN118969958B_ABST
Patent Text Reader

Abstract

The present invention relates to a battery pole piece surface microstructure, a preparation method and a device. A battery pole piece surface microstructure, wherein the battery pole piece surface has a groove with a groove depth to groove width ratio of 1:3-1:1, and the wetting contact angle of the battery pole piece with the groove is less than or equal to 40°, the groove depth is the distance between the deepest part of the groove and the battery pole piece surface, and the groove width is the size of the widest part of the groove. The present application processes grooves with a large groove depth to groove width ratio while ensuring that the grooves on the surface of the battery pole piece have good morphology through comprehensive and precise control of factors such as laser energy density, spot shape, and pulse duration, thereby forming a hydrophilic structure, improving the wettability of the battery pole piece, and generating a lithium ion fast channel, so that the embedding and de-embedding process of lithium ions in the positive and negative electrodes during the charging and discharging process is more efficient, thereby improving the comprehensive performance of the battery such as the charging and discharging speed, energy density, and capacity retention rate.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to a battery pole piece surface microstructure, in particular to a battery pole piece surface microstructure, a preparation method and a device. Background Art

[0002] Lithium batteries have good application prospects in aerospace, power transportation, consumer electronics and other fields due to their high energy density, long cycle life, high charge and discharge rate, and good safety. With the continuous growth of demand, all aspects of lithium-ion battery performance are facing new challenges, among which increasing energy density is one of the main research directions. The structure of lithium-ion batteries mainly includes positive electrode, negative electrode, electrolyte, diaphragm and shell, among which the positive and negative electrode structures are mainly composed of current collector and active material attached to the current collector. Increasing the thickness of the active material coating in the electrode is an effective way to increase the energy density of the battery. However, with the increase of the thickness of the pole piece, the transmission of lithium ions in the thick electrode slows down, the wetting of the electrolyte to the electrode active layer becomes difficult, the utilization rate of the electrode active material decreases accordingly, and the battery energy density decreases. For this reason, the prior art processes the surface of the pole piece, and the methods mainly include mechanical processing and laser processing. The mechanical processing methods in the currently disclosed technologies are mainly to set a pattern layer on the surface of the roller to imprint the pole piece, use metal mesh imprinting, mechanical punching, etc. Although these methods can obtain corresponding small holes or groove patterns, they will cause mechanical extrusion and mechanical stress to the material. In addition, the flexibility of the roller stamping processing method is limited, which is not conducive to processing different pole piece materials, and it is also impossible to change the processing according to different shape, depth and other requirements.

[0003] Prior art similar to the present invention: Currently, the relevant schemes for using laser processing methods to make microstructures on the surface of pole pieces mainly include innovative designs of laser systems and distribution and shape designs of microstructures on the surface of pole pieces. Prior art such as the surface treatment method and system for lithium-ion battery pole pieces (CN114497458A) designs a combined system including a spectrometer, a rotating mirror and a focusing lens, and stipulates a processing method for setting an isolator mask on the surface of the pole piece to form a plurality of processing holes or grooves distributed side by side at intervals, aiming to improve the processing efficiency of the surface structure of the pole piece: the laser is an infrared laser with a wavelength of 700 to 1500nm, and the etching structure includes a plurality of processing holes or grooves distributed side by side at intervals. It is worth noting that the specific processing dimensions of the pole piece microstructure, especially the ratio of the groove depth to the width, are crucial to the circulation and wetting of the electrolyte in the pole piece, but the application does not provide a detailed description of the specific process parameters of the etching holes / grooves and the depth, width and other dimensions of the holes / grooves, and it does not pay attention to the surface morphology of the battery pole piece after processing and the quality of the groove itself.

[0004] The difficulty in making a high aspect ratio pole piece microstructure lies in the diversity of pole piece material properties, the scientific selection of laser processing equipment, and the diversity of processing parameter combinations. Different pole piece materials contain different materials (positive electrode coating: ternary, lithium cobalt oxide, lithium iron phosphate; negative electrode coating: graphite, silicon-based materials, etc.), and each material pole piece contains different physical properties such as surface density, compaction density, particle size, thickness, etc. For different materials, it is necessary to match the appropriate type of laser processing system. If an unmatched laser system is selected, it may affect the chemical composition of the material. The interaction between the laser beam and the material surface may cause chemical reactions such as oxidation and reduction of the material (for example, oxides were found on the surface of the positive pole piece processed by infrared nanosecond and infrared continuous lasers). These chemical reactions may change the chemical composition and physical properties of the material, affect the corrosion resistance and mechanical properties of the material, and have a great impact on the performance and safety of the battery pole piece. In addition, improper selection of laser processing parameters will affect the microstructure of the pole piece. Under the action of laser, the surface of the pole piece is subjected to the action of high-energy heat source, which will form a rapid thermal cycle, which will cause phase change and lattice structure changes inside the material. If the laser process parameters are improperly selected and the energy density is too high, the crystal material will have problems such as grain rearrangement and grain boundary movement, and the amorphous material will have loose structure, which will further affect the mechanical properties of the battery pole piece. Laser processing will also cause residual stress to the microstructure of the pole piece. The high energy of the laser beam will cause local melting and expansion of the material. As the material cools rapidly, the temperature gradient and heat conduction difference inside the material will cause residual stress. The existence of residual stress may cause the generation and expansion of cracks in the pole piece, reducing the service life of the pole piece. Therefore, it is very difficult to obtain grooves with suitable structures while ensuring the quality of the grooves themselves when laser processing the microstructure of the pole piece. Summary of the invention

[0005] This application, through comprehensive and precise control of factors such as laser energy density, spot shape, and pulse duration, ensures that the grooves on the surface of the battery pole piece have good morphology, and processes grooves with a large groove depth and groove width ratio, forming a hydrophilic structure, improving the wettability of the battery pole piece, and generating a lithium ion fast channel, so that the embedding and de-embedding process of lithium ions in the positive and negative electrodes during the charging and discharging process is more efficient, thereby improving the comprehensive performance of the battery such as the charging and discharging speed, energy density, and capacity retention rate. There are three advantages in making the electrode surface microstructure. First, it shortens the electrolyte infiltration time in the battery process, especially when using thick pole pieces, it is easier to achieve full infiltration; secondly, it can effectively form an electrolyte transport channel during battery use, which is conducive to improving the lithium ion diffusion rate, shortening the charging time, and realizing high-rate charging; finally, after the battery is charged at a high rate, it can effectively inhibit the negative electrode lithium precipitation and extend the battery life when used in fast charging. In addition, constructing a microstructure on the pole piece surface can effectively avoid or reduce the cracks and powdering of the pole piece due to repeated contraction and expansion, thereby improving the battery cycle performance. On the basis of constructing the grooves, further improving the ratio of groove depth to groove width can reduce the loss of active materials, increase the amount of active material retained, and reduce the cost of battery production, which is of great significance.

[0006] To achieve the above-mentioned purpose, the present invention provides the following technical solutions: a battery pole piece surface microstructure, wherein the battery pole piece surface has a groove with a groove depth to groove width ratio of 1:3-1:1, and the wetting contact angle of the battery pole piece with the groove is less than or equal to 40°, the groove depth is the distance between the deepest part of the groove and the battery pole piece surface, and the groove width is the size of the widest part of the groove.

[0007] Furthermore, the depth of the groove ranges from 20 μm to 70 μm, and the width ranges from 20 μm to 140 μm.

[0008] Furthermore, the cross-sectional shape of the groove is triangular, rectangular, arc-shaped, stepped, or trapezoidal.

[0009] Furthermore, the grooves are arranged in parallel or in a grid-like cross arrangement, and the distances between the grooves are equal or unequal.

[0010] Furthermore, the plurality of parallel-arranged grooves are arranged in a straight-line parallel manner, a fold-line parallel manner, or an arc-line parallel manner.

[0011] A method for preparing the above-mentioned battery pole piece surface microstructure, using laser processing to form the battery pole piece surface microstructure;

[0012] The laser wavelength is 355nm-1550nm, the repetition frequency is 1kHz-2MHz, and the laser power is 200W-4000W;

[0013] For positive electrode materials, picosecond pulse laser or femtosecond laser is used for processing, and the pulse width is 300fs~10ps. Specifically, the laser pulse width should be selected to be smaller than the electroacoustic relaxation time of the material;

[0014] For negative electrode materials, nanosecond lasers or continuous fiber lasers are used for processing, with a pulse width of 100ns~200ns and a laser beam quality of M 2 ≤1.3, laser power range is between 200W~4000W.

[0015] Furthermore, the laser spot types include basic Gaussian spot, flat-top spot, annular spot, concentric multi-annular spot, and petal-shaped spot. Gaussian spot is used to construct grooves with triangular and arc-shaped cross-sections, flat-top spot is used to construct grooves with rectangular and trapezoidal cross-sections with smooth edges and lower heat impact, and annular spot and concentric multi-annular spot are used to construct grooves with stepped cross-sections.

[0016] A device for manufacturing the above-mentioned battery pole piece surface microstructure includes a first winding system for feeding, a first laser system for etching the front side of the battery pole piece, a second laser system for etching the back side of the battery pole piece, a 2D visual inspection system for detecting grooves, a first caching system for caching, a 3D visual inspection system for detecting grooves, a second caching system for caching, a labeling system for marking unqualified grooves, and a second winding system for receiving materials.

[0017] Furthermore, the first laser system and the second laser system include 8 lasers respectively, which are arranged in two columns, with 4 lasers in each column. Each column of lasers is equipped with a chiller, and every 2 lasers are equipped with a control system.

[0018] The beneficial effects of this application are:

[0019] The grooves with a large groove depth to groove width ratio in the present application form a hydrophilic structure, which improves the wettability of the battery pole piece and generates a lithium ion fast channel, making the embedding and de-embedding process of lithium ions in the positive and negative electrodes more efficient during the charging and discharging process, thereby improving the comprehensive performance of the battery such as the charging and discharging speed, energy density and capacity retention rate. BRIEF DESCRIPTION OF THE DRAWINGS

[0020] Figure 1 Schematic diagram of laser etching of the surface microstructure of the battery pole piece of the present invention, wherein the left figure is a schematic diagram of processing, and the right figure is a schematic diagram of the processed groove;

[0021] Figure 2Schematic diagram of the groove cross section of the microstructure of the battery pole piece surface of the present invention, wherein (a) is a triangle, (b) is a rectangle, (c) is an arc, (d) is a step, and (e) is a trapezoid;

[0022] Figure 3 Schematic diagram of the groove arrangement of the surface microstructure of the battery pole piece of the present invention, wherein (a) is a straight-line parallel arrangement, (b) is a folded-line parallel arrangement, (c) is an arc-line parallel arrangement, (d) is a straight-line parallel arrangement with unequal distances; and (e) is a grid-shaped cross arrangement;

[0023] Figure 4 Schematic diagram of the light spot types of the method for preparing the surface microstructure of the battery pole piece of the present invention, wherein (a) is an annular light spot, and (b) is a concentric multi-annular light spot;

[0024] Figure 5 It is a schematic diagram of a module of a device for manufacturing a microstructure on the surface of a battery electrode according to the present invention;

[0025] Figure 6 is a contact angle test diagram of Example 1 of the present invention;

[0026] Figure 7 is a laser confocal microscope image of the groove width of Example 1 of the present invention;

[0027] Figure 8 1 is a laser confocal microscope test diagram of the groove depth of Example 1 of the present invention, wherein a is a laser confocal microscope diagram of the groove depth, b is an enlarged diagram of a, and c is a groove depth test data diagram;

[0028] Fig. 9 is a contact angle test diagram of Example 2 of the present invention;

[0029] Fig.10 is a laser confocal microscope image of the groove width of Example 2 of the present invention;

[0030] Fig.11 1 is a laser confocal microscope test diagram of the groove depth of Example 2 of the present invention, wherein a is a laser confocal microscope diagram of the groove depth, b is an enlarged diagram of a, and c is a groove depth test data diagram;

[0031] Fig.12 is a laser confocal microscope image of the groove width of Example 3 of the present invention;

[0032] Fig.13 is a laser confocal microscope image of the groove depth of Example 3 of the present invention, wherein a is a laser confocal microscope image of the groove depth, b is an enlarged image of a, and c is a groove depth test data image;

[0033] Fig.141 is a laser confocal microscope test diagram of Example 4 of the present invention, wherein a is a laser confocal microscope diagram of groove depth, b is an enlarged diagram of a, c is a laser confocal microscope diagram of groove width, d is a contact angle test diagram, and e is a groove depth test data diagram;

[0034] Fig.15 is a laser confocal microscope test diagram of Example 9 of the present invention, wherein a is a laser confocal microscope diagram of groove depth, b is an enlarged diagram of a, c is a laser confocal microscope diagram of groove width, and d is a groove depth test data diagram;

[0035] Fig.16 It is a curve graph showing the change of contact angle with groove depth and groove width, wherein the abscissa is the ratio of groove depth to groove width, and the ordinate is the contact angle. DETAILED DESCRIPTION

[0036] In order to further explain the technical means and effects adopted by the present invention to achieve the predetermined invention purpose, the specific implementation mode, structure, characteristics and effects of the present invention are described in detail below in combination with the accompanying drawings and preferred embodiments.

[0037] The present application achieves comprehensive and precise control over factors such as laser energy density, spot shape, and pulse duration, and processes grooves with a large depth-to-width ratio while ensuring that the grooves on the surface of the battery pole piece have good morphology, thereby forming a hydrophilic structure, improving the wettability of the battery pole piece, and generating a lithium ion fast channel, making the embedding and de-embedding process of lithium ions in the positive and negative electrodes more efficient during the charge and discharge process, thereby improving the comprehensive performance of the battery, such as the charge and discharge speed, energy density, and capacity retention rate.

[0038] Example 1

[0039] A battery electrode surface microstructure, the battery electrode surface has a groove with a certain groove depth and groove width ratio, the groove depth is the distance between the deepest part of the groove and the battery electrode surface, and the groove width is the size of the widest part of the groove. Figure 2 In (b), the cross-sectional shape of the groove is a rectangle. Figure 3 In (a), the grooves are arranged in multiple parallel rows, and the multiple parallel grooves are arranged in a straight line and parallel manner, and the distances between the multiple grooves are equal.

[0040] A method for preparing the above-mentioned battery electrode surface microstructure, such as Figure 1 , laser processing is used to form the surface microstructure of the battery pole piece; a flat-top spot is used to construct a groove with a rectangular cross-section shape;

[0041] For the positive electrode material, the material in this embodiment is lithium cobalt oxide, and is processed using an ultraviolet picosecond laser with a laser wavelength of 355nm, a repetition frequency of 500kHz, a laser power of 20W, and a pulse width of 10ps. Specifically, a laser pulse width that is less than the electroacoustic relaxation time of the material should be selected for processing. In some embodiments, a continuous fiber laser can also be used.

[0042] like Figure 5 , a device for manufacturing the surface microstructure of the battery pole piece as mentioned above, including a first winding system for feeding, a first laser system for etching the front side of the battery pole piece, a second laser system for etching the back side of the battery pole piece, a 2D visual inspection system for detecting the groove, a first caching system for caching, a 3D visual inspection system for detecting the groove, a second caching system for caching, a labeling system for marking unqualified grooves, and a second winding system for receiving the material.

[0043] The first laser system and the second laser system include 8 lasers respectively, which are arranged in two columns, 4 lasers in each column. Each column of lasers is equipped with a chiller, and every 2 lasers are equipped with a control system.

[0044] like Figure 6 It can be seen that the wetting contact angle of the battery electrode produced in this embodiment is 12.799°.

[0045] like Figure 7 and Figure 8 It can be seen that the surface quality of the electrode plate processing groove is good, without cracks or spatter, the groove edge is smooth, the crater and heat impact are small, and there is no modification effect on the electrode material. The cross-sectional shape of the groove is rectangular, the groove width is 54.3μm, and the groove depth is 32.19μm. The ratio of the groove depth to the groove width in this embodiment is about 3:5.

[0046] The laser model used in this embodiment is: Knight-UV Laser Series: Knight-355-20W.

[0047] Example 2

[0048] A battery electrode surface microstructure, the battery electrode surface has a groove with a certain groove depth and groove width ratio, the groove depth is the distance between the deepest part of the groove and the battery electrode surface, and the groove width is the size of the widest part of the groove. Figure 2 In (b), the cross-sectional shape of the groove is a rectangle. Figure 3 In (b), the grooves are arranged in multiple parallel rows, and the multiple parallel grooves are arranged in a zigzag parallel pattern, and the distances between the multiple grooves are equal.

[0049] like Figure 1, a method for preparing the above-mentioned battery pole piece surface microstructure, using laser processing to form the battery pole piece surface microstructure; using a flat-top spot to construct a groove with a rectangular cross-sectional shape;

[0050] For the positive electrode material, the material in this embodiment is lithium iron phosphate, and is processed using an ultraviolet picosecond laser with a laser wavelength of 355nm, a repetition frequency of 1MHz, a laser power of 50W, and a pulse width of 5ps. Specifically, a laser pulse width that is less than the electroacoustic relaxation time of the material should be selected for processing. In some embodiments, a continuous fiber laser can also be used.

[0051] like Figure 5 , a device for manufacturing the surface microstructure of the battery pole piece as mentioned above, including a first winding system for feeding, a first laser system for etching the front side of the battery pole piece, a second laser system for etching the back side of the battery pole piece, a 2D visual inspection system for detecting the groove, a first caching system for caching, a 3D visual inspection system for detecting the groove, a second caching system for caching, a labeling system for marking unqualified grooves, and a second winding system for receiving the material.

[0052] The first laser system and the second laser system each include 8 lasers, which are arranged in two rows, 4 lasers in each row, each row of lasers is equipped with a chiller, and every 2 lasers are equipped with a control system. This embodiment uses ultraviolet picosecond lasers.

[0053] like Fig. 9 It can be seen that the wetting contact angle of the battery electrode produced in this embodiment is 37.622°.

[0054] like Fig.10 and Fig.11 It can be seen that the surface quality of the electrode plate processing groove is good, without cracks or spatter, the groove edge is smooth, the crater and heat impact are small, and there is no modification effect on the electrode material. The cross-sectional shape of the groove is rectangular, the groove width is 64.65μm, and the groove depth is 50.04μm. The ratio of the groove depth to the groove width in this embodiment is about 4:5.

[0055] The laser model used in this embodiment is: Knight-UV Laser Series: Knight-355-50W.

[0056] Example 3

[0057] A battery electrode surface microstructure, the battery electrode surface has a groove with a certain groove depth and groove width ratio, the groove depth is the distance between the deepest part of the groove and the battery electrode surface, and the groove width is the size of the widest part of the groove. Figure 2 In (b), the cross-sectional shape of the groove is a rectangle. Figure 3In (c), the grooves are arranged in multiple parallel rows, and the multiple parallel grooves are arranged in an arc-shaped parallel manner, and the distances between the multiple grooves are equal.

[0058] like Figure 1 , a method for preparing the above-mentioned battery pole piece surface microstructure, using laser processing to form the battery pole piece surface microstructure; using Gaussian spot to construct a groove with a rectangular cross-sectional shape;

[0059] For the positive electrode material, the material in this embodiment is lithium cobalt oxide, and an infrared femtosecond laser is used for processing, with a laser wavelength of 1064nm, a repetition frequency of 2MHz, a laser power of 30W, a pulse width of 300fs, and a laser beam quality of M 2 =1.3, continuous fiber lasers can also be used in some embodiments.

[0060] like Figure 5 , a device for manufacturing the surface microstructure of the battery pole piece as mentioned above, including a first winding system for feeding, a first laser system for etching the front side of the battery pole piece, a second laser system for etching the back side of the battery pole piece, a 2D visual inspection system for detecting the groove, a first caching system for caching, a 3D visual inspection system for detecting the groove, a second caching system for caching, a labeling system for marking unqualified grooves, and a second winding system for receiving the material.

[0061] The first laser system and the second laser system each include 8 lasers, which are arranged in two rows, 4 lasers in each row, each row of lasers is equipped with a chiller, and every 2 lasers are equipped with a control system. This embodiment uses an infrared femtosecond laser.

[0062] like Fig.12 and Fig.13 It can be seen that the surface quality of the electrode plate processing groove is good, without cracks or spatter, the groove edge is smooth, the crater and heat impact are small, and there is no modification effect on the electrode material. The cross-sectional shape of the groove is rectangular, the groove width is 60.83μm, the groove depth is 20.53μm, and the groove depth to groove width ratio of this embodiment is about 1:3.

[0063] The laser model used in this embodiment is: Kudos Ultrafast Laser Series: Kudos 1064-30W.

[0064] Example 4

[0065] A battery pole surface microstructure, the battery pole surface has a groove with a groove depth to groove width ratio of 1:1, the groove depth is the distance between the deepest part of the groove and the battery pole surface, and the groove width is the size of the widest part of the groove. The groove depth is 70μm and the width is 70μm. Figure 2In (b), the cross-sectional shape of the groove is a rectangle. Figure 3 In (d), the grooves are arranged in multiple parallel rows, the multiple parallel grooves are arranged in a straight line and parallel manner, and the distances between the multiple grooves are not equal.

[0066] like Figure 1 , a method for preparing the above-mentioned battery pole piece surface microstructure, using laser processing to form the battery pole piece surface microstructure; Figure 4 In (a), a groove with a stepped cross-sectional shape is constructed by using an annular light spot; in some embodiments, a groove with a stepped cross-sectional shape may also be constructed by using concentric multiple annular light spots;

[0067] For the negative electrode material, the material in this embodiment is graphite doped with silicon, and is processed using an ultraviolet nanosecond laser with a laser wavelength of 355 nm, a repetition frequency of 1 kHz, a laser power of 100 W, a pulse width of 200 ns, and a laser beam quality of M 2 =1.1.

[0068] like Figure 5 , a device for manufacturing the surface microstructure of the battery pole piece as mentioned above, including a first winding system for feeding, a first laser system for etching the front side of the battery pole piece, a second laser system for etching the back side of the battery pole piece, a 2D visual inspection system for detecting the groove, a first caching system for caching, a 3D visual inspection system for detecting the groove, a second caching system for caching, a labeling system for marking unqualified grooves, and a second winding system for receiving the material.

[0069] The first laser system and the second laser system include 8 lasers respectively, which are arranged in two columns, 4 lasers in each column. Each column of lasers is equipped with a chiller, and every 2 lasers are equipped with a control system.

[0070] like Fig.14 The surface quality of the electrode groove is good, without cracks or spatter, the groove edge is flat, the crater and heat influence are small, and there is no modification effect on the electrode material, wherein a is a laser confocal microscope image of the groove depth, b is a laser confocal microscope image of the groove width, c is an enlarged image of b, d is a contact angle test image, and e is a groove depth test data image; the cross-sectional shape of the groove is rectangular, the groove width is 99.59 μm, the groove depth is 54.25 μm, the groove depth to groove width ratio of this embodiment is about 1:2, and the wetting contact angle is 4.376°.

[0071] The laser model used in this embodiment is: keystone-355-100W.

[0072] Example 5

[0073] A battery pole surface microstructure, the battery pole surface has a groove with a groove depth to groove width ratio of 1:2, the groove depth is the distance between the deepest part of the groove and the battery pole surface, and the groove width is the size of the widest part of the groove. The groove depth is 20μm and the width is 40μm. Figure 2 In (a), the cross-sectional shape of the groove is a triangle. Figure 3 In (e), the grooves are arranged crosswise in a grid.

[0074] A method for preparing the above-mentioned battery electrode surface microstructure, such as Figure 1 , laser processing is used to form the surface microstructure of the battery pole piece; Gaussian spot is used to construct a groove with a triangular cross-sectional shape;

[0075] For the positive electrode material, the material in this embodiment is lithium cobalt oxide, and an infrared femtosecond laser is used for processing. The laser wavelength is 1550nm, the repetition frequency is 2kHz, the laser power is 100W, and the pulse width is 300fs. Specifically, a laser pulse width that is smaller than the electroacoustic relaxation time of the material should be selected for processing.

[0076] like Figure 5 , a device for manufacturing the surface microstructure of the battery pole piece as mentioned above, including a first winding system for feeding, a first laser system for etching the front side of the battery pole piece, a second laser system for etching the back side of the battery pole piece, a 2D visual inspection system for detecting the groove, a first caching system for caching, a 3D visual inspection system for detecting the groove, a second caching system for caching, a labeling system for marking unqualified grooves, and a second winding system for receiving the material.

[0077] The first laser system and the second laser system include 8 lasers respectively, which are arranged in two columns, 4 lasers in each column. Each column of lasers is equipped with a chiller, and every 2 lasers are equipped with a control system.

[0078] The laser model used in this embodiment is: Kudos Ultrafast Laser Series: Kudos -1550-100W.

[0079] Example 6

[0080] A battery pole surface microstructure, the battery pole surface has a groove with a groove depth to groove width ratio of 1:2, the groove depth is the distance between the deepest part of the groove and the battery pole surface, and the groove width is the size of the widest part of the groove. The groove depth is 70μm and the width is 140μm. Figure 2 In (b), the cross-sectional shape of the groove is a rectangle. Figure 3 In (b), the grooves are arranged in multiple parallel rows, and the distances between the multiple grooves are equal. The multiple parallel grooves are arranged in parallel in a zigzag pattern.

[0081] like Figure 1 , a method for preparing the above-mentioned battery pole piece surface microstructure, using laser processing to form the battery pole piece surface microstructure; using a flat-top spot to construct a groove with a rectangular cross-sectional shape;

[0082] For the positive electrode material, the material in this embodiment is lithium iron phosphate, and an infrared picosecond laser is used for processing. The laser wavelength is 1064nm, the repetition frequency is 1MHz, the laser power is 30W, and the pulse width is 10ps. Specifically, a laser pulse width that is smaller than the electroacoustic relaxation time of the material should be selected for processing.

[0083] like Figure 5 , a device for manufacturing the surface microstructure of the battery pole piece as mentioned above, including a first winding system for feeding, a first laser system for etching the front side of the battery pole piece, a second laser system for etching the back side of the battery pole piece, a 2D visual inspection system for detecting the groove, a first caching system for caching, a 3D visual inspection system for detecting the groove, a second caching system for caching, a labeling system for marking unqualified grooves, and a second winding system for receiving the material.

[0084] The first laser system and the second laser system include 8 lasers respectively, which are arranged in two columns, 4 lasers in each column. Each column of lasers is equipped with a chiller, and every 2 lasers are equipped with a control system.

[0085] The laser model used in this embodiment is: Kudos Ultrafast Laser Series: Kudos -1064-100W.

[0086] Example 7

[0087] A battery pole surface microstructure, the battery pole surface has a groove with a groove depth to groove width ratio of 1:1, the groove depth is the distance between the deepest part of the groove and the battery pole surface, and the groove width is the size of the widest part of the groove. The groove depth is 20μm and the width is 20μm. Figure 2 In (c), the cross-sectional shape of the groove is an arc. Figure 3 In (c), the grooves are arranged in multiple parallel rows, and the multiple parallel grooves are arranged in an arc-shaped parallel manner, and the distances between the multiple grooves are equal.

[0088] like Figure 1 , a method for preparing the above-mentioned battery pole piece surface microstructure, using laser processing to form the battery pole piece surface microstructure; using Gaussian spot to construct a groove with an arc-shaped cross-section shape;

[0089] For the negative electrode material, the material in this embodiment is graphite, and a continuous fiber laser is used for processing. The laser wavelength is 1064nm. The continuous fiber laser has no repetition frequency and pulse width. The laser power is 4000W, and the laser beam quality M 2 =1.2.

[0090] like Figure 5 , a device for manufacturing the surface microstructure of the battery pole piece as mentioned above, including a first winding system for feeding, a first laser system for etching the front side of the battery pole piece, a second laser system for etching the back side of the battery pole piece, a 2D visual inspection system for detecting the groove, a first caching system for caching, a 3D visual inspection system for detecting the groove, a second caching system for caching, a labeling system for marking unqualified grooves, and a second winding system for receiving the material.

[0091] The first laser system and the second laser system include 8 lasers respectively, which are arranged in two columns, 4 lasers in each column. Each column of lasers is equipped with a chiller, and every 2 lasers are equipped with a control system.

[0092] The laser model used in this embodiment is: Knight-LCG-4000W.

[0093] Example 8

[0094] A battery pole surface microstructure, the battery pole surface has a groove with a groove depth to groove width ratio of 1:1, the groove depth is the distance between the deepest part of the groove and the battery pole surface, and the groove width is the size of the widest part of the groove. The groove depth is 70μm and the width is 70μm. Figure 2 In (d), the cross-sectional shape of the groove is a step shape. Figure 3 In (d), the grooves are arranged in multiple parallel rows, and the distances between the multiple grooves are different. The multiple parallel grooves are arranged in a straight line.

[0095] like Figure 1 , a method for preparing the above-mentioned battery pole piece surface microstructure, using laser processing to form the battery pole piece surface microstructure; Figure 4 In (b), a groove with a stepped cross-sectional shape is constructed by using concentric multi-annular light spots; in some embodiments, a groove with a stepped cross-sectional shape may also be constructed by using concentric multi-annular light spots;

[0096] For the negative electrode material, the material in this embodiment is graphite doped with silicon, and an infrared nanosecond laser is used for processing, with a laser wavelength of 1064nm, a repetition frequency of 500kHz, a laser power of 1000W, a pulse width of 100ns, and a laser beam quality of M 2 = 1.2. In some embodiments, 200 ns may also be used.

[0097] like Figure 5 , a device for manufacturing the surface microstructure of the battery pole piece as mentioned above, including a first winding system for feeding, a first laser system for etching the front side of the battery pole piece, a second laser system for etching the back side of the battery pole piece, a 2D visual inspection system for detecting the groove, a first caching system for caching, a 3D visual inspection system for detecting the groove, a second caching system for caching, a labeling system for marking unqualified grooves, and a second winding system for receiving the material.

[0098] The laser model used in this embodiment is: Kudos Ultrafast Laser Series: Kudos 1064-1000W.

[0099] Example 9

[0100] A battery electrode surface microstructure, the battery electrode surface has a groove with a certain groove depth and groove width ratio, the groove depth is the distance between the deepest part of the groove and the battery electrode surface, and the groove width is the size of the widest part of the groove. Figure 2 In (b), the cross-sectional shape of the groove is a rectangle. Figure 3 In (a), the grooves are arranged in parallel and the distances between the grooves are equal. The grooves arranged in parallel are arranged in a straight line.

[0101] A method for preparing the above-mentioned battery electrode surface microstructure, such as Figure 1 , laser processing is used to form the surface microstructure of the battery pole piece; a flat-top spot is used to construct a groove with a rectangular cross-section shape;

[0102] For the positive electrode material, the material in this embodiment is nickel-cobalt-manganese, and is processed using a green picosecond laser with a laser wavelength of 532 nm, a repetition frequency of 1 MHz, a laser power of 70 W, and a pulse width of 10 ps.

[0103] like Figure 5 , a device for manufacturing the surface microstructure of the battery pole piece as mentioned above, including a first winding system for feeding, a first laser system for etching the front side of the battery pole piece, a second laser system for etching the back side of the battery pole piece, a 2D visual inspection system for detecting the groove, a first caching system for caching, a 3D visual inspection system for detecting the groove, a second caching system for caching, a labeling system for marking unqualified grooves, and a second winding system for receiving the material.

[0104] The first laser system and the second laser system include 8 lasers respectively, which are arranged in two columns, 4 lasers in each column. Each column of lasers is equipped with a chiller, and every 2 lasers are equipped with a control system.

[0105] like Fig.15 It can be seen that the surface quality of the electrode plate processing groove is good, without cracks or spatter, the groove edge is smooth, the crater and heat impact are small, and there is no modification effect on the electrode material. The cross-sectional shape of the groove is rectangular, the groove width is 39.58μm, and the groove depth is 39.27μm. The ratio of the groove depth to the groove width in this embodiment is about 1:1.

[0106] The laser model used in this embodiment is: Knight-Green Laser Series: Knight-532-70W-1M.

[0107] like Fig.16 ,As the ratio of groove depth and width increases, the wetting contact angle decreases, indicating that increasing the ratio of groove depth and width is beneficial to the infiltration of electrolyte into the electrode sheet, thereby improving the charge and discharge performance of the battery.

[0108] The present application achieves comprehensive and precise control of factors such as laser energy density, spot shape, pulse duration, etc., and processes grooves with a large depth-to-width ratio while ensuring that the grooves on the surface of the battery pole piece have good morphology, thereby forming a hydrophilic structure with a small contact angle, improving the wettability of the battery pole piece, and generating a lithium ion fast channel, making the embedding and de-embedding process of lithium ions in the positive and negative electrodes more efficient during the charge and discharge process, thereby improving the comprehensive performance of the battery, such as the charge and discharge speed, energy density, and capacity retention rate.

[0109] The above description is only a preferred embodiment of the present invention and does not limit the present invention in any form. Although the present invention has been disclosed as a preferred embodiment as above, it is not used to limit the present invention. Any technical personnel in this field can make some changes or modify the technical contents disclosed above into equivalent embodiments without departing from the scope of the technical solution of the present invention. However, any brief modifications, equivalent changes and modifications made to the above embodiments based on the technical essence of the present invention without departing from the content of the technical solution of the present invention are still within the scope of the technical solution of the present invention.

Claims

1. A method for preparing a battery electrode surface microstructure, characterized in that: The battery pole piece is a negative electrode, the negative electrode material is graphite doped with silicon or graphite, the surface of the battery pole piece has a groove with a groove depth to groove width ratio of 1:3-1:1, and the wetting contact angle of the battery pole piece with the groove is less than or equal to 40°, the groove depth is the distance between the deepest part of the groove and the surface of the battery pole piece, and the groove width is the size of the widest part of the groove; the surface microstructure of the battery pole piece is formed by laser processing; Nanosecond laser or continuous fiber laser is used for processing. When nanosecond laser is used for processing, the laser wavelength is 355nm-1064nm, the repetition frequency is 1kHz-500kHz, the pulse width is 100ns~200ns, and the laser beam quality M 2 ≤1.3, the laser power range is between 100W and 4000W; when continuous fiber laser is used for processing, the laser wavelength is 355nm-1064nm, and the laser beam quality M 2 ≤1.3, the laser power range is between 100W and 4000W; the laser spot types include Gaussian spot, flat-top spot, annular spot, concentric multi-annular spot or petal-shaped spot. The Gaussian spot is used to construct a groove with a triangular or arc-shaped cross-section, the flat-top spot is used to construct a groove with a rectangular or trapezoidal cross-section, and the annular spot or concentric multi-annular spot is used to construct a groove with a stepped cross-section.

Citation Information

Patent Citations

  • Lithium ion battery pole piece surface treatment method and system

    CN114497458A

  • Laser adding method and equipment for lithium ion battery negative electrode high-capacity element material

    CN114284474A

  • Three-dimensional electrode manufacturing method based on efficient ion diffusion

    CN114883520A

  • Lithium ion battery electrode plate and lithium ion battery

    CN203932198U